An Investigation of the Optimum Solar Flux Distribution on a Large-Scale Particle Heating Receiver - El-Leathy, Abdelrahman; Al-Ansary, Hany; Danish, Syed Noman; Alsuhaibani, Anas; Alswaiyd, Abdulelah (Frontiers in Energy Research, 2022)
Solid particles have been shown to be an effective heat transmission as well as thermal storage medium for falling particle receiver based solar power systems at temperatures up to 1,000°C. The temperature distribution on the surface of the falling particle receiver is critical. High temperatures, thermal shocks, and temperature gradients produce substantial stresses on the receiver due to high, fluctuating, and non-homogeneous solar flux. To this effect, the optimum control of the heliostats’ aiming points is one of the obstacles that must be overcome. The flux distribution on the receiver surface must be carefully managed to avoid dangerous flux peaks or excessive temperature gradients which might result in local hot spots resulting in damage of the receiver’s internal components over time. To overcome this problem, specifying multiple aiming points on the receiver aperture may control the solar flux distribution. In this study both single and multi aiming points strategies are applied by assigning a group of heliostats to a specific aim point on the receiver, resulting in a uniform flux distribution over the receiver surface. Engineering software packages SolarPILOT, SOLTRACE and MATLAB are used in combination to get the optimal flux distribution. The results showed that the flux distribution is improved significantly after employing the multi aiming points strategy at the expense of greater spillage.